Perkembangan Teknologi Kesehatan di Era Society 5.0 - Levina Lintang Pramita; Aji Wibawa (Universitas Ngeri Malang, 2022)
There are so many fields that is important for human being, and Healthcare is one of those fields, because having a healthy and fit body allows people to do their daily well. Health technology that exists today will definitely have an increasement in the next era, i.e. Society 5.0 era which initiated by Japan. The enhancement of healthcare technology in the coming years aims to improve our personal health standards, leading to better overall well-being for humanity at large scale. The improvement of health technology in the Society 5.0 era can occur due to the improvement of technology itself, starting from AI, robots, 3D printing, and information technology. Indeed, these four technologies are already present in the current era, but they are expected to experience significant growth in the Society 5.0 era, thereby becoming crucial components in various domains, including the healthcare sector. The deployment of these four technologies has a significant influence on the development of novel healthcare technologies, such as disease detection using Artificial Intelligence, robots for medical operations and other medical services, the existence of artificial organs that created by 3d printing, long-distance health services, and the implantation of microchips for health purposes. Kesehatan dianggap sebagai salah satu aspek yang paling penting dalam hidup manusia, karena memiliki tubuh yang sehat dan bugar memungkinkan individu untuk menjalankan aktivitas harian mereka dengan lancar. Teknologi kesehatan yang ada pada saat ini pasti akan mengalami peningkatan di era selanjutnya, yaitu Era Society 5.0 yang dicetuskan oleh Jepang. Peningkatan teknologi kesehatan di masa depan bertujuan untuk peningkatan kualitas kesehatan kita sendiri yang berdampak pada kesejahteraan manusia pada lingkup yang luas. Peningkatan teknologi kesehatan di Era Society 5.0 terjadi karena adanya peningkatan teknologi itu sendiri, mulai dari AI, robot, 3d Printing, dan Teknologi informasi. Sebenarnya, keempat teknologi tersebut sudah ada saat ini, namun pada Era Society 5.0, teknologi tersebut akan memiliki peningkatan yang sangat tinggi sehingga memiliki peran penting dalam semua bidang, termasuk bidang kesehatan. Penerapan keempat teknologi tersebut berdampak pada munculnya teknologi kesehatan baru, misalnya pendeteksian penyakit menggunakan Artificial Intelligent, robot untuk operasi dan pelayanan medis lainnya, adanya organ buatan, layanan kesehatan jarak jauh, serta penanaman chip mikro untuk kepentingan kesehatan.